Associations of parental birth characteristics with autism spectrum disorder (ASD) risk in their offspring: a population-based multigenerational cohort study in Denmark. (7th January 2021) - Xiao, Jingyuan; Gao, Yu; Yu, Yongfu; Toft, Gunnar; Zhang, Yawei; Luo, Jiajun; Xia, Yuntian; Chawarska, Katarzyna; Olsen, Jørn; Li, Jiong; Liew, Zeyan
Abstract: Background: Fetal exposure risk factors are associated with increased autism spectrum disorder (ASD) risk. New hypotheses regarding multigenerational risk for ASD have been proposed, but epidemiological evidence is largely lacking. We evaluated whether parental birth characteristics, including preterm birth and low birthweight, were associated with ASD risk in offspring. Methods: We conducted a nationwide register-based cohort study that included 230 174 mother-child and 157 926 father-child pairs in Denmark. Logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (CI) for offspring ASD according to parental preterm (<37 weeks) and low birthweight (<2500 g) status, with or without adjustment for certain grandmaternal sociodemographic factors. Mediation analyses were performed for selected parental and offspring health-related factors. Results: Offspring of mothers or fathers with adverse birth characteristics had about 31–43% higher risk for ASD (maternal preterm birth, OR = 1.31, 95% CI= 1.12, 1.55; maternal low birthweight, OR = 1.35, 95% CI: 1.17, 1.57; paternal preterm birth, OR = 1.43, 95% CI = 1.18, 1.73; paternal low birthweight, OR = 1.38, 95% CI= 1.13, 1.70). Parents born very preterm (<32 weeks) marked a nearly 2-fold increase in ASD risk in their children. These associations were slightly attenuated upon adjustment for grandmaternal sociodemographic factors. Mediation analyses suggested that parental social-mental and offspring perinatal factors might explain a small magnitude of the total effect observed, especially for maternal birth characteristic associations. Conclusions: Offspring of parents born with adverse characteristics had an elevated risk for ASD. Transmission of ASD risk through maternal and paternal factors should be considered in future research on ASD aetiology.